Potential and Challenges for the Clinical Use of d-Serine As a Cognitive Enhancer - Guercio, Gerson D.; Panizzutti, Rogerio (Frontiers in Psychiatry, 2018)
After 25 years of its discovery in the rat brain, D-serine is a recognized modulator of synaptic plasticity and cognitive processes through its actions on the NMDA-glutamate receptor. Importantly, cognitive impairment is a core feature of conditions such as schizophrenia, Alzheimer’s disease, depression and aging, and is associated to disturbances in NMDA-glutamate receptors. The D-serine pathway has been associated with cognitive deficits and these conditions, and, for this reason, D-serine signaling is subject of intense research to probe its role in aiding diagnosis and therapy. Nevertheless, this has not resulted in new therapies being incorporated into clinical practice. Therefore, in this review we will address many questions that need to be solved by future studies, regarding D-serine pharmacokinetics, possible side-effects, other strategies to modulate its levels and combination with other therapies to increase its efficacy.